Structural differentiation of skeletal muscle fibers in the absence of innervation in humans - Boncompagni, Simona (National Academy of Sciences, 2007)
The relative importance of muscle activity versus neurotrophic factors in the maintenance of muscle differentiation has been greatly debated. Muscle biopsies from spinal cord injury patients, who were trained with an innovative protocol of functional electrical stimulation (FES) for prolonged periods (2.4–9.3 years), offered the unique opportunity of studying the structural recovery of denervated fibers from severe atrophy under the sole influence of muscle activity. FES stimulation induced surprising recovery of muscle structure, mass, and force even in patients whose muscles had been denervated for prolonged periods before the beginning of FES training (up to 2 years) and had almost completely lost muscle-specific internal organization. Ninety percent (or more) of the fibers analyzed by electron microscopy showed a striking recovery of the ultrastructural organization of myofibrils and Ca(2+)-handling membrane systems. This functional/structural restoration follows a pattern that mimics some aspects of normal muscle differentiation. Most importantly, the recovery occurs in the complete absence of motor and sensory innervation and of nerve-derived trophic factors, that is, solely under the influence of muscle activity induced by electrical stimulation.